LEGAL PROTECTION IMPLEMENTATION FOR DISABILITIES PERSONS IN OBTAINING EQUAL EMPLOYMENT OPPORTUNITIES IN DENPASAR CITY - Intan Safira Morgana; I Made Dedy Priyanto (Transpublika Publisher, 2022)
This research aims to identify and comprehend the regulatory arrangements for employees with physical disabilities to get opportunity equality, as well as the implementation of legal protection for workers with physical disabilities to obtain equal job opportunities in the city of Denpasar. The study approach utilized is an empirical legal research method based on a comparison between das sollen and das sein. Legal and fact-based approaches are applied. Primary data sources include interviews with disabled workers in the city of Denpasar, whereas secondary data sources include statutes and regulations, books, and scientific journals. According to the findings, the regulation regarding persons with disabilities is clearly stated in the national regulations, namely the Human Rights Law, the Law on Persons with Disabilities, and the Manpower Act, whereas the special regulations for Denpasar City are contained in the Bali Provincial Regulation on Persons with Disabilities. However, despite the fact that there are policies in place to govern persons with disabilities in Denpasar City, it is still difficult to find a job, especially in companies, due to the stigma that people with disabilities are incapable of doing anything. Even though the state has enacted legislation governing the employment of people with disabilities, the reality of the situation makes these regulations difficult to implement, especially in relation to issues of employment.